Kinerja Produksi Benih Ikan Jelawat (Leptobarbus hoevenii Blkr) Dengan Ketinggian Air Berbeda Pada Sistem Resirkulasi - Eko Harianto; Muarofah Ghofur; M Sugihartono; Aldi Aldi (Jurnal Akuakultur Sungai dan Danau, 2023)
This study aims to determine the optimal water level for the rearing of jelawat fish (Leptobarbus hoevenii blkr) with a recirculation system. This research was conducted for 60 days at the Telanaipura Ornamental Fish Installation Laboratory, Jambi Province Maritime Affairs and Fisheries Service. The study was conducted using a completely randomized design with 4 treatments and 3 replications covering a water level of 10 cm (A), a water level of 15 cm (B), a water level of 20 cm (C) and a water level of 25 cm (D). The results showed that the different water level treatments had a significant effect (P<0.05) on survival rate (SR), absolute weight growth (AWG) and feed conversion (FC). The highest percentage of survival was in treatment D (water level 25 cm) of 95.62%. The average SR value tends to increase with the increasing water content of the rearing medium. The lowest SR value was found in treatment A (water level 10 cm) of 87.38%. The average weight of fish at the beginning of the study was 0.12 ± 0.005 g/head, increasing at the end of the study to 0.88 ± 0.048 g/head. The average absolute lenght growth (ALG) and AWG ranged between 1.83g - 2.31g and 1.83g - 2.31g, respectively. The highest FC value was in treatment A (water level 10 cm) of 1.93 and the lowest FC value was in treatment C and D (water level 20 and 25 cm) of 0.79. Blood glucose values at the beginning of the study ranged from 44.33 mg/dL – 56.00 mg/dL while at the end of the study the blood glucose values decreased and ranged from 40.33 mg/dL – 45.00 mg/dL. The results of the analysis of the water quality of the rearing medium show that the water quality is still in the feasible range for the maintenance of barnet fish